How to become a Brahman: The construction of varṇa as social place in the Mahābhārata’s legends of Viśvāmitra - Sathaye, Adheesh (Acta Orientalia Vilnensia, 2007)
University of British ColumbiaThis article investigates varṇa as an embodied and spatialized social practice in the Sanskrit Mahābhārata, with a focus on the epic subnarratives of Viśvāmitra, the legendary king who became a Brahman. Adopting a post-Dumontian position that the articulation of social status is always a political act, the Mahābhārata’s treatment of Viśvāmitra is analyzed as a literary attempt to secure the social place of Brahmanhood in post-Mauryan India. Two specific narratives are taken up for comparative study: first the kāmadhenu legend—the squabble with Vasiṣṭha that led to Viśvāmitra’s Brahmanhood—and then an altogether different story in which a mixup by Viśvāmitra’s sister Satyavatī meant that he had always been a Brahman by birth. Two distinct interpretive voices are heard in the same epic—one extolling Viśvāmitra’s extraordinary ascetic power, and another, louder one minimizing his realworld impact by insisting that his varṇa change never actually happened. Developing the concept of ‘textual performance’ to explain how fluid legendary material was embedded into the fixed epic corpus, this article argues that the Mahābhārata utilized counter-normative figures like Viśvāmitra to articulate alternative voices and possibilities, but within a carefully regulated epic storyworld that naturalized varṇa as an everyday social practice.